1998
DOI: 10.1074/jbc.273.30.19183
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Casein Kinase 2 by Direct Interaction with Cell Surface Receptor CD5

Abstract: The transmembrane protein CD5, expressed on all T cells and the B1 subset of B cells, modulates antigen receptor-mediated activation. We used the yeast twohybrid system to identify proteins that interact with its cytoplasmic domain and play a role in CD5 proximal signaling events. We found that the ␤ subunit of the serine/threonine kinase casein kinase 2 (CK2) interacts specifically with the cytoplasmic domain of CD5. Coimmunoprecipitation experiments showed activationindependent association of CK2 with CD5 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
57
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 62 publications
2
57
0
Order By: Relevance
“…This interaction is mediated by the b regulatory subunit of CK2. Similar interactions with the b subunit have been reported for CK2-specific substrates: p53 (Filhol et al, 1992), FGF2 (Bonnet et al, 1996), DNA Topoisomerase IIa , CD5 (Raman et al, 1998), Nopp 140 (Li et al, 1997a) and the p21 protein (a CDK inhibitor) (Gotz et al, 2000;Romero-Oliva and Allende, 2001). It is clearly established that on binding to CK2b, CK2a changes activity and substrate specificity.…”
Section: Discussionmentioning
confidence: 62%
“…This interaction is mediated by the b regulatory subunit of CK2. Similar interactions with the b subunit have been reported for CK2-specific substrates: p53 (Filhol et al, 1992), FGF2 (Bonnet et al, 1996), DNA Topoisomerase IIa , CD5 (Raman et al, 1998), Nopp 140 (Li et al, 1997a) and the p21 protein (a CDK inhibitor) (Gotz et al, 2000;Romero-Oliva and Allende, 2001). It is clearly established that on binding to CK2b, CK2a changes activity and substrate specificity.…”
Section: Discussionmentioning
confidence: 62%
“…Upon CD3 ligation, the CD5 cytoplasmic tail becomes phosphorylated leading to the likely recruitment of p56 lck [33], PI3K [34], proto-oncoprotein c-Cbl, ras GTPase-activating protein [35] and SHP-1 [36]. In addition, CD5 ligation allows the activation of casein kinase II, which is constitutively associated to its cytoplasmic tail [37][38][39], as well as the activation of protein kinase C by a phosphatidylcholine-specific phospholipase C-dependent pathway [40]. Early in vitro studies indicated that CD5 acts as a costimulatory molecule for T-cell activation [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CD5 ligation allows the activation of casein kinase II, which is constitutively associated to its cytoplasmic tail [37][38][39], as well as the activation of protein kinase C by a phosphatidylcholine-specific phospholipase C-dependent pathway [40]. Early in vitro studies indicated that CD5 acts as a costimulatory molecule for T-cell activation [41,42].…”
mentioning
confidence: 99%
“…We have however observed that, contrary to the majority of CD5 À B cells, normal CD5 þ blood B cells displayed a low Ca 2 þ response following anti-IgM stimulation, 15 confirming the role of CD5 as a negative regulator of BCR signaling. 16,17 Even though BCR-mediated activation is often deficient in CLL, CD5 may act independently of the BCR by recruiting signaling molecules, 18,19 and eliciting the production of B-cell survival factors such as interleukin (IL)-10. 15 IL-10 is indeed produced by most CLL B-cells, 20 improves the survival of malignant CLL B-cells, 21 and IL-10 serum levels in CLL correlated with the severity of the disease.…”
Section: Introductionmentioning
confidence: 99%